A new material of double lanthanide metal doped NiO anode and application thereof

CN122889766APending Publication Date: 2026-10-09CHINA UNIV OF MINING & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610972166.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-01
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

镧系金属中未填充的d、f电子壳层可与Ni电子配合,但镧系金属较大的离子半径难以掺入NiO晶格,而且离子半径不匹配会导致晶胞过度膨胀,造成结构稳定性下降,高温易烧结现象

Benefits of technology

相比于现有技术,本发明具有如下优点:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889766A_ABST
    Figure CN122889766A_ABST
Patent Text Reader

Abstract

The application discloses a kind of double lanthanide series metal co-doped NiO anode material and application thereof.La ion and Pr ion are introduced into NiO crystal lattice by impregnation-ball milling combined process, and La-Pr co-doped NiO anode material (LPNO) is obtained.La ion and Pr ion partially replace Ni site in NiO crystal lattice, regulate NiO crystal structure, and improve the electronic structure and microstructure of the material.The direct coal fuel cell constructed by the anode material has a maximum power density of 422 mW·cm ‑2 at 800 DEG C, and has good electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention pertains to direct coal solid oxide fuel cells, specifically relating to a novel lanthanide-doped NiO anode material and its applications. Background Technology

[0002] Fossil fuels, represented by coal, are a crucial foundation for national development, but the energy crisis has spurred demand for the clean and efficient utilization of traditional fossil fuels. Direct coal fuel cells (DCFCs) can efficiently convert the chemical energy in solid fuels into electrical energy. Compared to traditional coal-fired power generation, their operation does not require heat engine energy conversion and is not limited by the Carnot cycle. NiO, due to its low cost, ease of synthesis, and well-defined redox behavior (Ni... 2+ / Ni 3+ With adjustable particle morphology, size, porosity, and specific surface area, it is widely used as anode material for DCFC. In existing technologies, traditional nickel-based fuel electrodes used in DCFC suffer from low oxygen vacancy content and poor C / CO selectivity, which greatly reduces the power generation efficiency of coal-based materials.

[0003] Currently, DCFC batteries using coal as fuel still largely use pure NiO as the anode material, without in-depth research on its intrinsic structure. Therefore, it is necessary to specifically modify NiO electrodes to significantly improve the compatibility and catalytic activity of NiO materials with other components. Incorporating lanthanide metal ions into transition metal oxides (TMOs) can adjust the morphology, lattice, and electronic configuration of the material. While the unfilled d and f electron shells in lanthanides can interact with Ni electrons, the large ionic radii of lanthanides make them difficult to incorporate into the NiO lattice. Furthermore, ionic radius mismatch can lead to excessive cell expansion, resulting in decreased structural stability and easy sintering at high temperatures. Therefore, how to introduce lanthanide metal ions to optimize the local electronic configuration of nickel and systematically regulate the catalytic activity of NiO is a pressing technical challenge in this field. Summary of the Invention

[0004] The purpose of this invention is to provide a defect engineering control strategy for dual lanthanide metals. Through a combined impregnation-ball milling process, La and Pr ions are introduced into the NiO lattice structure to prepare modified NiO anode materials. The La-Pr co-doped NiO anode electrode can significantly improve electrocatalytic activity, thereby further enhancing the performance of solid oxide fuel cells, effectively increasing the current intensity and power density, and improving cell stability.

[0005] The technical solution of this invention is as follows: La and Pr ions were introduced into the NiO lattice through a combined impregnation-ball milling process to prepare La-Pr co-doped NiO modified anode materials.

[0006] (1) Weigh 10g of nickel oxide (NiO) and add praseodymium nitrate (Pr(NO3)3·6H2O) and lanthanum nitrate (La(NO3)3·6H2O) respectively. The doping amount of La and Pr is required to be 4-6 mol of the molar amount of Ni.

[0007] (2) After stirring the above raw materials in deionized water for 2 hours, soak them for 8-16 hours, dry them at 80 °C, and then perform ultrasonic treatment for 30 minutes to prepare the required precursor powder.

[0008] (3) Add 20 mL of anhydrous ethanol to the precursor powder and place it in a 50 mL stainless steel grinding jar. Use a ball mill at a speed of 500 r·min -1 Continue ball milling for 12-48 hours to ensure that La and Pr ions are fully mixed with NiO.

[0009] (4) The above raw materials are dried overnight at 100 °C and calcined at 600-900 °C for 6-12 h to prepare the final product La-Pr co-doped NiO (abbreviated as LPNO).

[0010] (5) Using the commonly used tape casting, hot pressing, and high-temperature sintering technique in this field, yttrium-stabilized zirconium oxide (8YSZ) is prepared into a viscous slurry, coated and cooled using a tape casting machine to obtain a smooth solid layer. The solid layer is then compressed using a hot press and finally sintered in a 1450 ℃ high-temperature furnace to obtain an 8YSZ electrolyte sheet. Gadolinium-doped cerium oxide (GDC) is screen-printed on both sides of the 8YSZ electrolyte. After drying in an 80 ℃ oven, it is placed in a muffle furnace and sintered at 2 ℃·min. -1 The heating rate was increased to 800 °C and held for 3 h, then increased at 1 °C·min. -1 The heating rate was increased to 1400 °C and held for 5 h. After cooling to room temperature, GDC / 8YSZ / GDC was obtained. Then LSCF (La 0.8 Sr 0.2 Co 0.2 Fe 0.8 O 3+δ The screen is printed on one side of GDC / 8YSZ / GDC, and then sintered at 1150 ℃ to obtain GDC / 8YSZ / GDC / LSCF.

[0011] (6) The LPNO anode electrode is bonded to the GDC side of the solid electrolyte by sintering. The effective area of ​​the anode electrode is 0.2 cm². 2 .

[0012] (7) Attach the battery cells to one end of the corundum tube, use silver paste as a current collector, and connect it to both sides of the battery through silver wire. Keep the anode facing the inside of the corundum tube and expose the cathode to the air.

[0013] (8) Add 5g of coal to the corundum tube, seal the upper end of the corundum tube with a stopper, leaving a small vent hole. Then conduct an electrochemical test at 700-800 ℃.

[0014] Preferably, in step (1), Ni:La and Ni:Pr are 5 mol%; Preferably, the soaking time in step (2) is 12 h; Preferably, the ball milling time in step (3) is 24 h; Preferably, the calcination conditions in step (4) are 800 °C for 8 h; Compared with the prior art, the present invention has the following advantages: 1. This application further refines the design of the traditional NiO anode in solid oxide fuel cells, discovering that doped NiO (LPNO) undergoes lattice contraction, i.e., the Ni-O bonds exhibit local elongation and contraction characteristics, forming more fine pores. Although the specific surface area is not increased, the total pore size is effectively increased, and the coefficient of thermal expansion is lower than that of NiO, compared to YSZ electrolyte (approximately 10.5 × 10⁻⁶). -6 K -1 Highly matched; additionally, the valence state of Ni in the material is increased, Ni 3+ The proportion increased.

[0015] 2. The solid-state fuel cell prepared from the modified anode NiO (LPNO) material disclosed in this application can improve the power density of DCFC at 800 °C, achieving a power density as high as 422 mW·cm⁻¹ using anthracite as fuel. -2 And at 200mA·cm -2 It can operate continuously and stably for 35 hours at current density. Attached Figure Description

[0016] Figure 1 These are X-ray diffraction (XRD) patterns of the LPNO material prepared in Example 1 and LNO, PNO, and NiO in Comparative Examples 1, 2, and 3. Figure 2 This is a diagram showing the average Ni-O bond length of the LPNO material prepared in Example 1 and the LNO, PNO, and NiO in Comparative Examples 1, 2, and 3; Figure 3 The specific surface area analysis diagrams are of the LPNO material prepared in Example 1 and LNO, PNO, and NiO in Comparative Examples 1, 2, and 3. Figure 4 These are the Raman spectra of the LPNO material prepared in Example 1 and the LNO, PNO, and NiO in Comparative Examples 1, 2, and 3; Figure 5The graph shows the thermal expansion coefficients of the LPNO material prepared in Example 1 and the LNO, PNO, and NiO in Comparative Examples 1, 2, and 3. Figure 6 These are the synchrotron radiation spectra of the LPNO material prepared in Example 1 and the LNO, PNO, and NiO in Comparative Examples 1, 2, and 3; Figure 7 These are the power density diagrams of DCFC batteries prepared using LPNO as the anode in Examples 3-5; Figure 8 This is a power density diagram of the DCFC battery prepared using LNO as the anode in Comparative Example 4; Figure 9 This is a power density diagram of the DCFC battery prepared using PNO as the anode in Comparative Example 5; Figure 10 This is a power density diagram of the DCFC battery prepared using NiO as the anode in Comparative Example 6; Figure 11 These are DCFC stability test graphs from Example 5 and Comparative Example 7.

[0017] Note: In the attached diagram, NiO represents nickel oxide, LNO represents La-doped nickel oxide, PNO represents Pr-doped nickel oxide, and LPNO represents La-Pr co-doped NiO. Detailed Implementation

[0018] The technical solution of the present invention will be further described below with reference to the accompanying drawings, but it is not limited thereto. Any modifications or equivalent substitutions to the technical solution of the present invention that do not depart from the spirit and scope of the technical solution of the present invention should be covered within the protection scope of the present invention.

[0019] Example 1: Preparation of La-Pr co-doped nickel oxide (LPNO) La and Pr ions were introduced into the NiO lattice through a combined impregnation-ball milling process to prepare La and Pr co-doped NiO modified anode material LPNO, which was obtained through the following steps: (1) Weigh 10g of nickel oxide (NiO) and add 2.9g of praseodymium nitrate (Pr(NO3)3·6H2O) and 2.9g of lanthanum nitrate (La(NO3)3·6H2O) respectively. The comparison sample is pure NiO material.

[0020] (2) After stirring the above raw materials in deionized water for 2 hours, soak them for 8-16 hours, dry them at 80 °C, and then perform ultrasonic treatment for 30 minutes to prepare the required precursor powder.

[0021] (3) Add 20 mL of anhydrous ethanol to the precursor powder and place it in a 50 mL stainless steel grinding jar. Use a ball mill at a speed of 500 r·min -1Ball milling continued for 24 hours to ensure that La and Pr ions were fully mixed with NiO.

[0022] (4) The above raw materials were dried overnight at 100 °C and then calcined at 800 °C for 8 h to prepare the final product La-Pr co-doped NiO (abbreviated as LPNO).

[0023] The preparation of LNO is the same as above, except that one of the raw materials is lanthanum nitrate (La(NO3)3·6H2O). The preparation of PNO is the same as above, except that one of the raw materials is praseodymium nitrate (Pr(NO3)3·6H2O).

[0024] Example 2 Characterization of LPNO anode materials The LPNO anode material obtained in Example 1 was used as the experimental subject. X-ray diffraction (XRD) confirmed that the introduction of La / Pr into the NiO lattice caused relaxation shrinkage. Figure 1 Density functional theory (DFT) bond length simulations confirmed the distortion of the Ni-O bond and the relaxation of high-valence ions, resulting in a shortening of the average bond length. Figure 2 Specific surface area and porosity analyzer (BET) revealed that LPNO forms more fine pores, effectively increasing the total pore size without increasing the specific surface area. Figure 3 The blue shift of the Ni-O peak in LPNO in Raman spectroscopy indicates lattice contraction and shortening of Ni-O bonds. Figure 4 Thermal expansion meter tests revealed that LPNO has a lower coefficient of thermal expansion than NiO, and similar to YSZ electrolyte (approximately 10.5 × 10⁻⁶). -6 K -1 Highly matched Figure 5 The absorption edge of the LPNO catalyst in the synchrotron radiation spectrum shifts slightly to higher energies, indicating a slight increase in the average valence state of Ni. Figure 6 ).

[0025] Example 3: Preparation of DCFC battery using LPNO as anode material and testing of maximum power density at 800 °C The experimental steps in Examples 3-5 below are the same, but the results are different. The reason is that although the experimental steps are the same, the operating temperatures are different, namely 800, 750, and 700 ℃. Under different operating temperatures, the power density of the battery is different.

[0026] Using the commonly used tape casting, hot pressing, and high-temperature sintering technique in this field, (ZrO2) 0.92 (Y2O3) 0.08(8YSZ, Tianyao Co., Ltd, Qingdao, Shandong) was prepared into a viscous slurry, coated and cooled using a casting machine to obtain a smooth solid layer. The solid layer was then compressed using a hot press and finally sintered in a 1450 ℃ high-temperature furnace to obtain 8YSZ electrolyte sheets. Gadolinium-doped cerium oxide (GDC, Tianyao Co., Ltd, Qingdao, Shandong) was screen-printed on both sides of the 8YSZ electrolyte. After drying in an 80 ℃ oven, it was placed in a muffle furnace and heated at 2 ℃·min. -1 The heating rate was increased to 800 °C and held for 3 h, then increased at 1 °C·min. -1 The heating rate was increased to 1400 °C and held for 5 h. After cooling to room temperature, GDC / 8YSZ / GDC was obtained. Then LSCF (La 0.8 Sr 0.2 Co 0.2 Fe 0.8 O 3+δ (Tianyao Co., Ltd., Qingdao, Shandong) The GDC / 8YSZ / GDC / LSCF was obtained by screen printing on one side of the GDC / 8YSZ / GDC mixture and sintering at 1150 ℃. LPNO powder and 8YSZ were mixed and ball-milled at a mass ratio of 6:4, then screen-printed onto one side of the GDC / 8YSZ / GDC / LSCF mixture. After drying in an oven at 80 ℃, the mixture was placed in a muffle furnace and heated at 2℃·min. -1 The heating rate was increased to 800 °C and held for 4 h, then increased at 1 °C·min. -1 The temperature was increased to 1150 °C and held for 4 h. After cooling to room temperature, LPNO-YSZ / GDC / 8YSZ / GDC / LSCF solar cells were obtained. Silver paste was used as the current collector and connected to both sides of the cell via silver wire. One end of the corundum tube was sealed with sealant as a bonding and sealing material, keeping the LPNO anode facing the inside of the corundum tube, while the LSCF cathode was exposed to air. Subsequently, 5g of coal was added to the corundum tube, and the upper end of the quartz tube was sealed with a plug, leaving a small vent hole.

[0027] Using anthracite as the anode fuel and air as the cathode fuel gas, the DCFC with an LPNO anode prepared in this embodiment achieved a maximum power density of 422 mW·cm³ at 800 °C. -2 ( Figure 7 ).

[0028] Example 4: Maximum power density test of a DCFC battery using LPNO as the anode material at 750 °C. The DCFC battery prepared using LPNO as the anode material is the same as in Example 3.

[0029] Using anthracite as the anode fuel and air as the cathode fuel gas, the DCFC with an LPNO anode prepared in this embodiment achieved a maximum power density of 307 mW·cm³ at 750 °C. -2 ( Figure 7 ).

[0030] Example 5: Maximum power density test of a DCFC battery using LPNO as the anode material at 700 °C. The DCFC battery prepared using LPNO as the anode material is the same as in Example 3.

[0031] Using anthracite as the anode fuel and air as the cathode fuel gas, the DCFC with an LPNO anode prepared in this embodiment achieved a maximum power density of 211 mW·cm³ at 700 °C. -2 ( Figure 7 ).

[0032] Example 6: A DCFC battery using LPNO as the anode material at 200 mA·cm -2 Detection of steady-state operation time under current density The DCFC battery prepared using LPNO as the anode material is the same as in Example 3. Using anthracite as the anode fuel and air as the cathode fuel gas, the DCFC with the LPNO anode prepared in this example achieves a DCFC efficiency of 200 mA·cm⁻¹. -2 It can operate continuously and stably for 35 hours at current density.

[0033] Comparative Example 1: Characterization of La-doped NiO anode material (LNO) This embodiment uses La-doped NiO anode material (LNO) as the experimental material. XRD was used to determine the parameters in the NiO lattice. The expansion of the NiO lattice indicates that La metal ions were successfully incorporated into the NiO lattice. Density functional theory (DFT) bond length simulations showed that the overall twisting and elongation of the Ni-O bonds. A BET (Body Surface Area and Porosity Analyzer) showed that the specific surface area of ​​LNO was higher than that of NiO. A thermal dilatometer test showed that its coefficient of thermal expansion was higher than that of NiO. Raman spectroscopy confirmed the redshift of the Ni-O spectral peak in LNO. Synchrotron radiation spectroscopy determined the valence state of Ni ions in NiO. The average valence state of Ni ions in LNO was similar to that of +2 Ni ions in NiO.

[0034] Comparative Example 2: Characterization of Pr-doped NiO anode material (PNO) This embodiment uses Pr-doped NiO anode material (PNO) as the experimental object. XRD was used to determine the parameters in the NiO lattice. NiO lattice expansion indicates that Pr metal ions were successfully incorporated into the NiO lattice. Density functional theory (DFT) bond length simulations showed that the overall twisting and elongation of the Ni-O bonds. A BET (Body Surface Area and Porosity Analyzer) showed that the specific surface area of ​​PNO was higher than that of NiO. A thermal dilatometer test showed that the coefficient of thermal expansion was higher in PNO than in NiO. Raman spectroscopy confirmed the redshift of the Ni-O spectral peak in PNO. Synchrotron radiation spectroscopy determined the valence state of Ni ions in NiO. The average valence state of Ni ions in PNO was similar to that of +2 Ni ions in NiO.

[0035] Characterization of NiO anode material in Comparative Example 3 This embodiment uses NiO anode material as the experimental object. XRD was used to determine the parameters in the NiO lattice. Density functional theory (DFT) bond length simulation was used to calculate and observe the average Ni-O bond length. A surface area and porosity analyzer (BET) was used to analyze the porosity of the NiO material. A thermal dilatometer was used to measure the conventional thermal expansion coefficient of NiO. Raman spectroscopy was used to observe the normal Ni-O peak positions. Synchrotron radiation spectroscopy was used to determine the Ni ion valence state in NiO.

[0036] Comparative Example 4 used a DCFC battery prepared with LNO as the anode material as the experimental subject to determine the maximum power density at 700-800 °C. The DCFC battery prepared using LNO as the anode material was used as the experimental subject. The commonly used technique in this field, tape casting, hot pressing, and high-temperature sintering, was employed to prepare (ZrO2). 0.92 (Y2O3) 0.08 (8YSZ, Tianyao Co., Ltd, Qingdao, Shandong) was prepared into a viscous slurry, coated and cooled using a casting machine to obtain a smooth solid layer. The solid layer was then compressed using a hot press and finally sintered in a 1450 ℃ high-temperature furnace to obtain 8YSZ electrolyte sheets. Gadolinium-doped cerium oxide (GDC, Tianyao Co., Ltd, Qingdao, Shandong) was screen-printed on both sides of the 8YSZ electrolyte. After drying in an 80 ℃ oven, it was placed in a muffle furnace and heated at 2 ℃·min. -1 The heating rate was increased to 800 °C and held for 3 h, then increased at 1 °C·min. -1 The heating rate was increased to 1400 °C and held for 5 h. After cooling to room temperature, GDC / 8YSZ / GDC was obtained. Then LSCF (La 0.8 Sr 0.2 Co 0.2 Fe 0.8 O 3+δ(Tianyao Co., Ltd., Qingdao, Shandong) The GDC / 8YSZ / GDC was screen-printed on one side of the GDC / 8YSZ / GDC and sintered at 1150 ℃ to obtain GDC / 8YSZ / GDC / LSCF. LNO powder and 8YSZ were mixed at a mass ratio of 6:4, ball-milled, and then screen-printed onto one side of the GDC / 8YSZ / GDC / LSCF. After drying in an oven at 80 ℃, the mixture was placed in a muffle furnace and sintered at 2 ℃·min. -1 The heating rate was increased to 800 °C and held for 4 h, then increased at 1 °C·min. -1 The temperature was increased to 1150 °C and held for 4 h. After cooling to room temperature, LNO-YSZ / GDC / 8YSZ / GDC / LSCF solar cells were obtained. Silver paste was used as the current collector and connected to both sides of the cell via silver wires. One end of the corundum tube was sealed with sealant as a bonding and sealing material, keeping the anode (LNO side) facing the inside of the corundum tube, while the LSCF cathode was exposed to air.

[0037] Add 5g of anthracite to a corundum tube, seal the top of the quartz tube with a stopper, leaving a small vent hole. Using anthracite as the anode fuel and air as the cathode fuel gas, the DCFC with an LNO anode prepared in this embodiment achieved a maximum power density of 195 mW·cm³ at 800 °C. -2 ( Figure 8 ).

[0038] Comparative Example 5 used a DCFC battery prepared with PNO as the anode material as the experimental subject to determine the maximum power density at 700-800 °C. The DCFC battery prepared using PNO as the anode material was used as the experimental subject. The commonly used technique in this field, tape casting, hot pressing, and high-temperature sintering, was employed to prepare (ZrO2). 0.92 (Y2O3) 0.08 (8YSZ) was prepared into a viscous slurry, which was then coated and cooled using a casting machine to obtain a smooth solid layer. The solid layer was then compressed using a hot press and finally sintered in a 1450 ℃ high-temperature furnace to obtain 8YSZ electrolyte sheets. Gadolinium-doped cerium oxide (GDC, Tianyao Co., Ltd., Qingdao, Shandong) was screen-printed on both sides of the 8YSZ electrolyte. After drying in an 80 ℃ oven, it was placed in a muffle furnace and heated at 2 ℃·min. -1 The heating rate was increased to 800 °C and held for 3 h, then increased at 1 °C·min. -1 The heating rate was increased to 1400 °C and held for 5 h. After cooling to room temperature, GDC / 8YSZ / GDC was obtained. Then LSCF (La 0.8 Sr 0.2 Co 0.2 Fe 0.8 O 3+δ(Tianyao Co., Ltd., Qingdao, Shandong) PNO powder was screen-printed on one side of GDC / 8YSZ / GDC and sintered at 1150 ℃ to obtain GDC / 8YSZ / GDC / LSCF. PNO powder and 8YSZ were mixed at a mass ratio of 6:4, ball-milled, and then screen-printed on one side of GDC / 8YSZ / GDC / LSCF. After drying in an oven at 80 ℃, the mixture was placed in a muffle furnace and heated at 2 ℃·min. -1 The heating rate was increased to 800 °C and held for 4 h, then increased at 1 °C·min. -1 The temperature was increased to 1150 °C and held for 4 h. After cooling to room temperature, a PNO-YSZ / GDC / 8YSZ / GDC / LSCF solar cell was obtained. Silver paste was used as the current collector and connected to both sides of the cell via silver wires. One end of the corundum tube was sealed with sealant as a bonding and sealing material, keeping the PNO anode facing the inside of the corundum tube, while the LSCF cathode was exposed to air.

[0039] Add 5g of anthracite to a corundum tube, seal the top of the quartz tube with a stopper, leaving a small vent hole. Using anthracite as the anode fuel and air as the cathode fuel gas, the DCFC with the PNO anode prepared in this embodiment achieved a maximum power density of 302 mW·cm³ at 800 °C. -2 ( Figure 9 ).

[0040] Comparative Example 6 uses a DCFC battery prepared with NiO as the anode material as the experimental subject, and the maximum power density at 700-800 °C was measured. The DCFC battery prepared using NiO as the anode material was used as the experimental subject. The commonly used technique in this field, tape casting, hot pressing, and high-temperature sintering, was employed to prepare (ZrO2). 0.92 (Y2O3) 0.08 (8YSZ) was prepared into a viscous slurry, which was then coated and cooled using a casting machine to obtain a smooth solid layer. The solid layer was then compressed using a hot press and finally sintered in a 1450 ℃ high-temperature furnace to obtain 8YSZ electrolyte sheets. Gadolinium-doped cerium oxide (GDC, Tianyao Co., Ltd., Qingdao, Shandong) was screen-printed on both sides of the 8YSZ electrolyte. After drying in an 80 ℃ oven, it was placed in a muffle furnace and heated at 2 ℃·min. -1 The heating rate was increased to 800 °C and held for 3 h, then increased at 1 °C·min. -1 The heating rate was increased to 1400 °C and held for 5 h. After cooling to room temperature, GDC / 8YSZ / GDC was obtained. Then LSCF (La 0.8 Sr 0.2 Co 0.2 Fe 0.8 O 3+δ(Tianyao Co., Ltd., Qingdao, Shandong) The GDC / 8YSZ / GDC was screen-printed on one side of the GDC / 8YSZ / GDC and sintered at 1150 ℃ to obtain GDC / 8YSZ / GDC / LSCF. NiO powder and 8YSZ were mixed at a mass ratio of 6:4, ball-milled, and then screen-printed onto one side of the GDC / 8YSZ / GDC / LSCF. After drying in an oven at 80 ℃, the mixture was placed in a muffle furnace and sintered at 2 ℃·min. -1 The heating rate was increased to 800 °C and held for 4 h, then increased at 1 °C·min. -1 The temperature was increased to 1150 °C and held for 4 h. After cooling to room temperature, NiO-YSZ / GDC / 8YSZ / GDC / LSCF solar cells were obtained. Silver paste was used as the current collector and connected to both sides of the cell via silver wires. One end of the corundum tube was sealed with sealant as a bonding and sealing material, keeping the NiO anode facing the inside of the corundum tube, while the LSCF cathode was exposed to air.

[0041] Add 5g of anthracite to a corundum tube, seal the top of the quartz tube with a stopper, leaving a small vent hole. Using anthracite as the anode fuel and air as the cathode fuel gas, the DCFC prepared in this embodiment achieves a maximum power density of 135 mW·cm³ at 800 °C. -2 ( Figure 10 ).

[0042] Comparative Example 7: DCFC Stability Test A DCFC battery prepared using NiO, LNO, and PNO as anode materials was used as the experimental subject. 5g of anthracite was added to a corundum tube, and the upper end of the quartz tube was sealed with a stopper, leaving a small vent hole. Using anthracite as the anode fuel and air as the cathode fuel gas, the DCFC prepared in this comparative example achieved a speed of 200 mA·cm⁻¹. -2 It can operate continuously and stably for 8, 14, and 22 hours at current densities, respectively. Figure 11 ).

[0043] The above description is merely an embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural or procedural transformations made based on the content of the present invention specification, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.

Claims

1. A lanthanide-doped NiO anode material, characterized in that, The anode material includes a NiO matrix, in which La and Pr ions are co-doped in the NiO lattice. The La and Pr ions partially replace Ni sites to form a solid solution structure, wherein the doping amounts of La and Pr account for 4-6 mol of Ni sites, respectively.

2. The lanthanide-doped NiO anode material as described in claim 1, characterized in that, La and Pr each occupy 5 mol of Ni sites.

3. The lanthanide-doped NiO anode material as described in claim 1, characterized in that, La and Pr ions are doped into the NiO lattice by replacing Ni sites.

4. The lanthanide-doped NiO anode material as described in claim 1, characterized in that, The anode material is prepared by impregnation, ball milling and calcination of NiO and La and Pr sources.

5. The lanthanide-doped NiO anode material as described in claim 1, characterized in that, The anode material has a porous structure.

6. The lanthanide-doped NiO anode material as described in claim 4, characterized in that, The coefficient of thermal expansion of the anode material is lower than that of NiO, which is highly compatible with the YSZ electrolyte.

7. A method for preparing a lanthanide-doped NiO anode material as described in any one of claims 1-6, characterized in that, Includes the following steps: (1) Mix NiO with La source and Pr source, stir thoroughly in deionized water for 2 h, soak for 8-16 h, dry at 80 ℃, and then ultrasonically treat for 30 min to prepare the required precursor powder. (2) Add 20 mL of anhydrous ethanol to the precursor powder and place it in a ball mill at 500 r·min -1 Ball milling for 12-48 hours; (3) The ball-milled product was dried overnight at 100 °C and calcined at 600-900 °C for 6-12 h to prepare the final product La-Pr co-doped NiO (denoted as LPNO).

8. A solid oxide fuel cell, characterized in that, It includes an anode electrode, a solid electrolyte, and a cathode electrode arranged in sequence, wherein the anode electrode is the LPNO double lanthanide metal doped NiO electrode material described in claim 2.

9. A solid oxide fuel cell as described in claim 8, characterized in that, The following steps were taken to prepare the 8YSZ electrolyte sheet: (1) Yttrium-stabilized zirconia 8YSZ was prepared into a viscous slurry, coated and cooled by a casting machine to obtain a smooth solid layer, then the solid layer was compressed by a hot press, and finally sintered in a high-temperature furnace at 1450 °C to obtain an 8YSZ electrolyte sheet; gadolinium-doped cerium oxide (GDC) was screen-printed on both sides of the 8YSZ electrolyte; after drying in an oven at 80 °C, it was placed in a muffle furnace and sintered at 2 °C for 2 min. -1 The temperature was increased to 800 °C and held for 3 hours, then increased at a rate of 1 °C per minute. -1 The heating rate was increased to 1400 °C and held for 5 h. After cooling to room temperature, GDC / 8YSZ / GDC was obtained; then La... 0.8 Sr 0.2 Co 0.2 Fe 0.8 O 3+δ The LSCF is silkscreened on one side of GDC / 8YSZ / GDC and sintered at 1150 ℃ to obtain GDC / 8YSZ / GDC / LSCF. (2) The anode electrode LPNO is bonded to the solid electrolyte GDC side by sintering. The effective area of ​​the anode electrode is 0.2 cm². 2 ; (3) The battery cells are bonded to one end of the corundum tube, and silver paste is used as a current collector and connected to both sides of the battery through silver wire; the anode is kept facing the inside of the corundum tube and the cathode is exposed to the air.

10. A solid oxide fuel cell as described in claim 9, characterized in that, The anode electrode, solid electrolyte, and cathode electrode are all circular, with an effective area of ​​0.2 cm². 2 .

11. A solid oxide fuel cell as described in claim 9, characterized in that, Using anthracite as fuel, the power density reaches as high as 422 mW·cm³. -2 .